Corn Cost-Return Budget in Northeast Kansas - O'Brien, Daniel M.; Duncan, Stewart R.; Dhuyvetter, Kevin C. (My University, 2014)
This publication projects a budget that reflects expected income and costs based on typical corn production practices in northeastern Kansas.
MF571_2014_02
Keywords: MF571; Economics; Crops; MF